Reimagining Brand Loyalty through Consumer Narratives in the Age of Micro-Influencers - Megawati, Dewi; Jentot Tugiyono; Antonius, Romualdus (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2026)
The transformation of the digital marketing landscape has placed micro-influencers as important actors in shaping consumer narratives that impact brand loyalty. Brand loyalty, which was previously understood as limited to emotional attachment and repetitive buying behaviors, now needs to be redefined in the context of narrative-based digital interactions. This study aims to analyze how consumer narratives mediated by micro-influencers play a role in building, strengthening, or even shifting the form of brand loyalty in the social media era. The research method uses a descriptive qualitative approach with narrative analysis through case studies on two brands that actively collaborate with micro-influencers. Data was collected through in-depth interviews with 12 consumer informants and observations of relevant social media content, then analyzed thematically to identify patterns of meaning and narrative construction. The results show that consumer narratives articulated through micro-influencers tend to be perceived as more authentic, create emotional closeness, and strengthen consumer trust in brands. In addition, micro-influencers function as mediators that bridge consumers' personal experiences with brand identities, thus forming loyalty that is not only transactional, but also relational and symbolic. The study's conclusions confirm that brand loyalty in the digital age no longer relies on direct promotion, but rather on the power of credible and participatory narratives. Theoretically, this research contributes to the expansion of the understanding of narrative-based brand management, while practically providing strategic implications for managing collaborations with micro-influencers to increase consumer loyalty.